The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.12991/jrp.2018.81
|View full text |Cite
|
Sign up to set email alerts
|

Licorice cream promotes full-thickness wound healing in Guinea pigs

Abstract: Impaired wound healing may cause economic and social problems and seriously reduce the quality of life. The uses of herbal medicines as new alternative treatments are under investigation. This study investigated the effect of Glycyrrhiza glabra L. extract on the full-thickness wound healing in Guinea Pig model. Eight male Guinea Pigs (700-800 g) were used to be creared a square full-thickness wound with 1.5 ×1.5 dimensions on the lumbodorsal area. The wounds were randomly divided into four groups: I; control, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The tendency of licorice treatment to stimulate cell proliferative activity was previously observed in different in vitro (36,37) , animal (38,39) as well as clinical models (40) . In contrast, it's interesting to notice that licorice had been shown to cause apoptosis and cell cycle arrest in various cancer cell line types, exerting an anticancer impact (41,42) .…”
Section: Discussionmentioning
confidence: 72%
“…The tendency of licorice treatment to stimulate cell proliferative activity was previously observed in different in vitro (36,37) , animal (38,39) as well as clinical models (40) . In contrast, it's interesting to notice that licorice had been shown to cause apoptosis and cell cycle arrest in various cancer cell line types, exerting an anticancer impact (41,42) .…”
Section: Discussionmentioning
confidence: 72%
“…Similarly, Oloumi et al examined the effect of Licorice root extract on dermal wounds in rats and the study revealed an increase in the number of fibroblasts, in addition to better re-epithelialization in Licorice-treated groups when compared to control groups [ 56 ]. Moreover, Hanafi et al also documented that Licorice creams significantly improved wound healing in Guinea pigs [ 57 ]. Furthermore, Najeeb and Al-Refai reported that Licorice root extract can shorten the healing time of induced oral mucosal wounds in rabbits [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…G. Glabra, or Licorice, a native of south-east Europe and south-west Asia, was one of the widely used herbal medicine and a traditionally used flavoring/aromatic and calming plant that belongs to the family Papilionaceae/Fabaceae. [ 13 ] G. Glabra is a herbaceous perennial that may reach a height of 1 m. It has pinnate leaves that are 715 cm long and have 9-17 leaflets.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, they found the neovascularization, epidermal formation, and collagen deposition were significantly improved by the application of G. Glabra extracts at different concentrations in the wounds when compared to the controls. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%